Prevalence of intestinal parasites and associated factors among patients with HIV/AIDS at the anti-retroviral treatment clinic of Mizan-Tepi University Teaching Hospital, Southwest Ethiopia - Abayneh, Mengistu; Habtemariam, Yosef; Duguma, Tadesse; Abera, Mitiku (Frontiers in Public Health, 2024)
BackgroundIntestinal parasitic infections remain very common, particularly in areas with a high prevalence of immune-compromised patients, such as HIV/AIDS patients. The purpose of this study was to determine the prevalence of intestinal parasites and associated factors in people living with HIV/AIDS at an ART clinic in Mizan-Tepi University Teaching Hospital, southwest Ethiopia.MethodA cross-sectional survey was conducted from July to September 2021. A total of 191 adult people living with HIV/AIDS participated in this study. Data on socio-demographic, clinical, and other risk factors were collected using a structured questionnaire. Stool samples were collected and processed using a direct wet mount, formol-ether concentration, and modified Ziehl-Nelson staining techniques. The data were analyzed using the Statistical Package for Social Sciences Version 25 software.ResultsAmong 67 adult individuals living with HIV/AIDS, the prevalence of intestinal parasites was 35.1%. Specifically, 31.5% (45/143) of patients on antiretroviral therapy (ART) and 45.8% (22/48) of ART-naïve patients were infected. The distribution of intestinal parasites was as follows: protozoa were found in 14.7% of ART-treated patients and 22.9% of ART-naïve patients; helminths in 15.4% of ART-treated patients and 16.7% of ART-naïve patients; and opportunistic parasites in 1.4% of ART-treated patients and 6.25% of ART-naïve patients. Significant associations with a higher prevalence of intestinal parasites were observed for a CD4 count <200 cells/mm3 (Adjusted Odds Ratio [AOR] = 3.77; 95% Confidence Interval [CI]: 1.01–13.15; p = 0.04), consumption of unwashed raw vegetables (AOR = 3.29; 95% CI: 1.23–8.86; p = 0.02), and residing in rural areas (AOR = 2.34; 95% CI: 1.27–4.32; p = 0.01).ConclusionThe findings indicate that a significant proportion of adults living with HIV/AIDS are affected by intestinal parasites, with a notably higher prevalence among ART-naïve patients compared to those on ART. Factors such as a low CD4 count, consumption of unwashed raw vegetables, and rural residence are associated with increased risk of intestinal parasite infections. These results underscore the importance of improving hygiene practices and access to healthcare, particularly in rural areas, to reduce the burden of parasitic infections among individuals living with HIV/AIDS.